ANALYSIS OF THE EFFECT OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION ON PATIENT LOYALTY, WITH SERVICE QUALITY AND PATIENT SATISFACTION AS MEDIATING VARIABLES (A Study of Patients at the Dental and Oral Health Clinic of the Poncol Community Health Center in Magetan Regency) - Dyah Ayu Mustikaningsih; Adya Hermawati; Muchlis Mas’ud; Asih Tri Rachmi; Choirul Anam (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the effect of Total Quality Management (TQM) implementation on patient loyalty with service quality and patient satisfaction as mediating variables at the Dental and Oral Polyclinic of Poncol Health Center, Magetan Regency. This research is motivated by the phenomenon of fluctuating patient revisit rates that showed a declining trend throughout 2025, indicating problems in maintaining patient loyalty. This research employed a quantitative approach with a cross-sectional design. The population consisted of all patients who made revisit visits to the Dental and Oral Polyclinic of Poncol Health Center during the period January-December 2025, totaling 441 people. The sample size was determined using the Slovin formula with a 5% margin of error, resulting in 137 respondents. The sampling technique used purposive sampling. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.6.6 software. The results showed that: (1) TQM has no direct effect on patient loyalty; (2) TQM has a positive and significant effect on service quality; (3) TQM has a positive and significant effect on patient satisfaction; (4) service quality has a positive and significant effect on patient loyalty; (5) patient satisfaction has no significant effect on patient loyalty; (6) service quality is proven to mediate the effect of TQM on patient loyalty; and (7) patient satisfaction is not proven to mediate the effect of TQM on patient loyalty. These findings reinforce TQM theory (Deming, 1986) and SERVQUAL theory (Parasuraman et al., 1988) which emphasize the importance of quality management implementation in improving service quality, which ultimately can shape patient loyalty. Practically, health center management is advised to focus efforts on improving service quality, particularly on aspects of environmental comfort, service speed, and medical staff interaction with patients, as well as ensuring that every system improvement can be applied to real services that are directly felt by patients.